1989
DOI: 10.1007/bf02464912
|View full text |Cite
|
Sign up to set email alerts
|

ThePSO4 gene is responsible for an error-prone recombinational DNA repair pathway inSaccharomyces cerevisiae

Abstract: The induction of mitotic gene conversion and crossing-over in Saccharomyces cerevisiae diploid cells homozygous for the pso4-1 mutation was examined in comparison to the corresponding wild-type strain. The pso4-1 mutant strain was found to be completely blocked in mitotic recombination induced by photoaddition of mono- and bifunctional psoralen derivatives as well as by mono- (HN1) and bifunctional (HN2) nitrogen mustards or 254 nm UV radiation in both stationary and exponential phases of growth. Concerning th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In addition, it has also long been implicated in diverse genome maintenance pathways such as DNA interstrand crosslink-, DSB-and transcription-coupled repair and in the replication stress response (Chanarat and Sträßer, 2013). Indeed, human PRPF19 was first identified in S. cerevisiae as Pso4, whose loss sensitizes yeast to several genotoxins, particularly to DNA interstrand crosslinkinducing agents (Henriques et al, 1989;Rodrigues de Andrade et al, 1989;da Silva et al, 1995;Gray et al, 1996;Revers et al, 2002). In addition, mammalian cells deficient of PRPF19 display a pronounced sensitivity to DSB-inducing agents such as ionizing radiation and etoposide (Mahajan and Mitchell, 2003;Beck et al, 2008;Abbas et al, 2014).…”
Section: Rna-binding Proteins Promote Double-strand Break Repair Via Non-homologous End-joiningmentioning
confidence: 99%
“…In addition, it has also long been implicated in diverse genome maintenance pathways such as DNA interstrand crosslink-, DSB-and transcription-coupled repair and in the replication stress response (Chanarat and Sträßer, 2013). Indeed, human PRPF19 was first identified in S. cerevisiae as Pso4, whose loss sensitizes yeast to several genotoxins, particularly to DNA interstrand crosslinkinducing agents (Henriques et al, 1989;Rodrigues de Andrade et al, 1989;da Silva et al, 1995;Gray et al, 1996;Revers et al, 2002). In addition, mammalian cells deficient of PRPF19 display a pronounced sensitivity to DSB-inducing agents such as ionizing radiation and etoposide (Mahajan and Mitchell, 2003;Beck et al, 2008;Abbas et al, 2014).…”
Section: Rna-binding Proteins Promote Double-strand Break Repair Via Non-homologous End-joiningmentioning
confidence: 99%
“…Accordingly, xs9 was renamed pso4-1 as it was non-allelic to the other three psoralen-sensitive strains described at the time [ 28 , 29 ]. pso4-1 is also sensitive to UV, nitrogen mustard and methyl methane sulfonate, is hypomutable when exposed to these genotoxins and has impaired mitotic recombination (gene conversion and crossing over) [ 30 , 31 ]. Further mechanistic studies showed that incision at psoralen-induced crosslinks occurred normally in pso4-1 mutants but the recombination-mediated rejoining step was impaired.…”
Section: Prp19/pso4 An Rna Processing Factor and Dna Damage Response ...mentioning
confidence: 99%
“…In this regard, it was recently proposed that RFWD3 interacts with and promotes PCNA ubiquitylation to regulate replication fork progression and translesion synthesis [ 118 , 119 , 120 ]. Whether PRP19 also participates in DNA damage tolerance pathways remains an open question but it is interesting that in yeast, Prp19/Pso4 promotes mitotic recombination while also participating in error-prone repair of DNA lesions [ 29 , 30 , 32 ]. Thus, in response to replication stress, the NTC transforms into a sensor of RPA-ssDNA and functions as a ubiquitin ligase to promote ATR signaling and fork repair.…”
Section: The Ntc Promotes Atr Activationmentioning
confidence: 99%
“…That a protein can accomplish two different tasks within the cell is no big surprise. Prp19 was first identified as Pso4, a gene required in S. cerevisiae to support error-prone recombinational DNA repair [ 150 ]. This role was later extended to human cells [ 151 , 152 ].…”
Section: How Lipids Impact Nuclear Homeostasismentioning
confidence: 99%